Anđeo štitonoša s grbom obitelji de Judicibus – djelo nepoznatog suradnika Bonina Jakovljeva iz Milana - Marković, Predrag (Array, 2014)
Sažetak: Bonino di Jacopo da Milano occupies a significant place in Dalmatian sculpture of the first half of the fifteenth century. In a relatively short period of time during which he was active – less than twenty years – this master managed to create numerous carvings and sculptures in almost every major Dalmatian town. Despite the fact that in the last ten years or so, a number of new and rather important works have been attributed to Bonino, while the works of a lesser quality have been identified as being produced by his collaborators, the assessment of this Lombard sculptor as an artist has remained the same and is based on the arguments put forward by Milan Prelog (1961) which portray him as having a backward looking, essentially Romanesque, understanding of the human figure and limited creative abilities. Because of this, he tends to be considered responsible for the works of a lesser quality with the major exception of a high relief depicting an angel bearing the coat of arms of the de Judicibus family from the bell tower of Split Cathedral (Fig. 1). The relief, now at the Museum of the City of Split, comes from the ground floor of the Cathedral bell tower where it stood on its south side. It replaced by a replica during the restorations works in the late nineteenth and early twentieth century. The first scholar who identified it as part of Bonino’s oeuvre or, more specifically, as a work of one of his assistants, was Cvito Fisković (1950). In contrast to this, earlier researchers such as A. Venturi (1908), H. Folnescis (1914), and Ljubo Karaman (1936) considered the relief to be more stylistically advanced and connected it to the mid-fifteenth century artistic activity of Juraj Dalmatinac. Since Ljubo Karaman (1954) maintained his initial opinion even after C. Fisković’s attribution and softened his estimation only slightly, C. Fisković went on to attribute the angel from the bell tower to Bonino himself in a later, somewhat more detailed, discussion of the works this sculptor produced in Split (1969). He pointed out that the angel may well have been produced around 1426-1427 when the ground floor of the bell tower was being consolidated and when, as we learn from the sources, Bonino was working on the ciborium of St Domnius for the local Cathedral. Even a superficial comparison between the angel from the bell tower and the angels on Bonino’s ciborium (Fig. 2) reveals not only significant differences in the modelling technique, but, even more importantly, a completely different feeling for sculptural form. The angel with the de Judicibus coat of arms comes across as being dynamic in the available pictorial space and as having a far livelier facial expression as well as physical impostation all of which demonstrate that the noted discrepancies in style, chronology, and attribution are not accidental. The figure of the de Judicibus angel gentler, slimmer and more graceful than those made by Bonino and was brought to life by a slight turn of his small round head featuring full cheeks and resting on a thin, slightly elongated neck which is not found on Bonino’s angels. Significant differences are also evident in the angels’ hair: the hair on the de Judicibus angel is lush and somewhat unnaturally pulled up from the face so that it resembles a wig. Particularly lively are his large drilled eyes and a faint smile which hovers at the corners of his mouth – a feature absent from Bonino’s figures. Almost identical features as on this serene and lovely face can be found in the sepia preparatory sketch of St Matthew on the vault of the ciborium of St Domnius (Fig. 4) which is why it is logical to assume that the masters responsible for its completion or painting in 1429 – Dujam Vučković and Giovanni di Pietro da Milano – also made the preparatory drawing which served as a model for the de Judicibus angel from the bell tower. Close analogies with the angels on Bonino’s ciborium, another obvious source of inspiration, point to the fact that the artist responsible for the angel holing the de Judicibus coat of arms should be sought among Bonino’s close assistants as C. Fisković had initially suggested. A different role of the angels, that is, the predominantly religious one in the case of the angels on the ciborium above the altar of the local patron saint, and the mostly secular location of the angel on the bell tower sheds more light on the circumstances in which the de Judicibus angel may have been produced. One of the members of the de Judicibus family, a local noble family, was the Archbishop of Split Domnius II (1415-1420) who began raising funds for the completion of the bell tower in 1416 and who appointed a certain master Tvrdoj as the foreman but he never started the job. Dissatisfied with the passing of Split into Venetian hands in 1420, Archbishop Domnius left for Hungary where he stayed at the court of King Sigismund until his death in 1435. This information was used by Lj. Karaman to disprove the argument that the angel was made during Bonino’s sojourn at Split because he thought that the new Venetian government would not have allowed the installing of the coat of arms belonging to this self-exiled archbishop. Given that the coat of arms does not feature the episcopal mitre and cross, as noted by C. Fisković, it cannot be interpreted as belonging to him. In addition, the fact that this bishop is mentioned on the sarcophagus of his mother which was placed in the peripter of the Cathedral in 1429 clearly demonstrates that political reasons did not prevent the family connection with this bishop from being displayed. Moreover, the angel relief was carved on a large stone block which was organically linked to the masonry meaning that it was made during the consolidation of the ground floor of the bell tower carried out by Bonino’s workshop. Although the issue of authorship does not depend on the exact date of the angel relief, conspicuous similarities with the figure of St Matthew on the vault of the ciborium of St Domnius open up the possibility that the angel may have been produced during 1428, after Bonino went to Šibenik to work on the portal of the future Cathedral of St James. This might help explain a certain freedom of expression which is evident in the de Judicibus angel and which is absent from other works produced by Bonino’s workshop. Regardless of these circumstances surrounding what might be called hidden, political and subversive artistic freedom, perhaps acquired at a later date, evident in the de Judicibus angel, the main reasons for the angel’s lively movement and dynamism within the pictorial space lie in the fact that this relief expresses a completely different visual aesthetics and sculptural poetics when compared to the angels on the Cathedral ciborium. This is also corroborated by the capital above the angel’s head (Fig. 5). The capital’s intensely curling leaves distance it from Bonino’s variations of the ‘northern’ vegetal ornaments which can be seen on the capitals of the ciborium of St Domnius and bring it closer to the Venetian capitals with lush and curling leaves which appeared a decade or two later. The strong movement and the restless, somewhat extroverted, artistic hand apparent on this capital – not on display but the replica can be seen on the Cathedral bell tower – is also present in the de Judicibus angel which leaves no doubt that the two were made by the same sculptor. The aforementioned stylistic characteristics enable us to attribute another work to this unnamed master, that is, the statue of St Michael in the atrium of the Episcopal Palace at Šibenik (Fig. 6). If we take a closer look at the head of St Michael and his full round cheeks but also at the way his thick and pulled-up hair is depicted, we can easily recognize the hand of the same sculptor who made the de Judicibus angel. St Michael’s thin waist and his tense limbs which are bent as if made of rubber together with the tautened smooth surface of his armour have resulted in the unusual appearance of a body which seems to be hovering. The impression that the limbs are not in harmony with each other and that they were mechanically attached to the torso is achieved mostly by the right leg which is bent at the knee and depicted in profile. It is obvious that the unnamed master wanted to depict the traditional iconographic type of St Michael as a frontally placed heavenly soldier, which he could have seen in the monumental relief of St Michael set in the town walls next to the land gate, in a new, livelier and more dynamic, way. However, the execution clearly demonstrates that this ambition to achieve a more convincing and dramatic representation of the battle greatly exceeded the sculptor’s creative abilities. Despite everything, his clumsy attempt displays the same youthful and confident passion, unspoiled by routine and seen in the de Judicibus angel, for a more modern approach to the pictorial expression and for bringing a breath of fresh air into conventional iconographic schemes. Based on all the above, I believe that we can agree with the suggestion that, apart from the already identified Master of St Peter, the circle of Bonino di Jacopo da Milano nurtured another unnamed master. Although his oeuvre is not large, the works of this master are nevertheless significant and symptomatic of a new moment in the local sculpture of the early fifteenth century. This moment corresponds to the time when, at the very end of the 1430s, Dalmatian sculpture finally attempted to break free from the visual patterns and aesthetic formulae which were deeply rooted in the Trecento and which were transmitted by Bonino da Milano throughout the Dalmatian coast. Nevertheless, because he was limited by and tied to the old models as well as being dependent on his teacher, this young and ambitious assistant of Bonino marks the end of the old era rather than the beginning of the new one which would be announced in around ten years’ time by the arrival of yet another sculptor from Lombardy – Pietro di Martino da Milano.